Mechanism of adipocyte hormone secretion (leptin and resistin) - Goh, Kian Hong. (2009)
Adipose, which was regarded as a passive storage of excess energy (fat), have recently been recognized as a highly active endocrine organ secreting several signal molecules called adipokines. These included leptin and resistin which are critically involved in metabolic disorders. The functions and secretion of leptin and resistin are intimately linked. Both were being controlled by diet. Fasting reduced the serum levels of both adipokines while food intake achieved the opposite [1, 2, 3, 4]. Both adipokines inhibited differentiation of adipocytes [5, 6] and thus development of adipose tissue. They also encouraged angiogenesis [7, 8] and regulated immune responses [9, 10]. However, in some cases, they antagonized with each other such as increased insulin sensitivity by leptin [11] whereas resistin decreased it [3, 12, 13]; leptin reduced gluconeogenesis [14] whereas resistin promoted it [4, 15]; leptin enhanced JAK/Stat3 mediated signal transduction while resistin decreased it [16, 17]. Despite numerous studies, the secretion mechanisms and crosstalks between leptin and resistin remained poorly elucidated. Using TIRFM (total internal reflection fluorescence microscopy) and confocal microscopy on living adipocytes differentiated from 3T3-L1 fibroblasts, evidences pointed that both adipokines were compartmentalized into seperate vesicles. These vesicles did not co-localize with rab5 (marker of early endosomes) or Glut-4 (glucose transporter-4) containing vesicles. In addition, it was found that the secretion of leptin and resistin and the trafficking of leptin and resistin vesicles were oppositely regulated by insulin and protein kinase A. And interestingly, these adipokines adversely influence each other on their secretion and vesicle trafficking.